The Impact of The Existence of Religious Tourism on the Economy of the Surrounding Community Study on Three Religious Tourism Objects in Tuban - Rokhadi Rokhadi; Sukistanto Sukistanto; Heri Tugas Setyawati (Eduvest - Journal of Universal Studies, 2025)
This study explores the impact of religious tourism on the local communities' economy surrounding three key religious tourism sites in Tuban, East Java: the Sunan Bonang Tomb, Asmoro Qondi Tomb, and Kwan Sing Bio Temple. The main issue addressed is the underutilization of religious tourism's economic potential in these areas, where micro, small, and medium enterprises (MSMEs) still struggle to innovate and grow. The research evaluates how religious tourism contributes to local economic development through increased income, job creation, business innovation, and infrastructure improvements. Employing a qualitative method, data were collected through in-depth interviews, observations, documentation, and focus group discussions, and were analyzed using the Miles and Huberman model alongside SPSS-assisted regression analysis. The findings indicate that religious tourism significantly boosts the local economy, especially by encouraging entrepreneurship and improving the performance of MSMEs. However, challenges such as unequal benefit distribution and environmental management persist. The implications of this research emphasize the need for stakeholders to engage in strategic planning to enhance community participation, infrastructure, and innovation, thereby ensuring that religious tourism not only preserves cultural heritage but also becomes a sustainable driver of inclusive economic growth in the region.